A policy brief on improving reproductive and maternity services utilisation among women of reproductive age in Nigeria - Bolarinwa, Obasanjo; Tadokera, Rebecca; Tiwari, Ritika (Frontiers in Global Women's Health, 2025)
Nigeria continues to struggle with high maternal and child mortality despite its large economy. Reproductive and maternity services are underutilised, contributing to poor maternal and newborn outcomes. Barriers include geographic, socio-demographic, and economic factors. Northern and south-south regions show particularly low service utilisation. Young maternal age, low education, rural location, and Hausa ethnicity are key socio-demographic barriers. Non-Christian religious affiliation and limited mass media exposure also reduce service uptake. Poverty, unemployment, and lack of health insurance are major economic challenges. Community engagement and culturally sensitive care are essential. The use of religious and traditional leaders for advocacy could improve outreach. Expanding insurance and financial incentives, like vouchers or cash transfers, can reduce cost-related barriers